1140 CLINICAL OUTCOME OF FRACTIONAL FLOW RESERVE GUIDED REVASCULARIZATION STRATEGY OF CORONARY LESIONS: THE HALE-BOPP STUDY. (15th December 2022) - Caglioni, Serena; Campo, Gianluca; Gallo, Francesco; Scoccia, Alessandra; Durante, Alessandro; Tedeschi, Delio; Verdoliva, Sebastiano; Cortese, Bernardo; Bilotta, Ferruccio; Watkins, Stuart; Ielasi, Alfonso; Valentini, Giuliano; et al.
Abstract: Background: There are currently some doubts about the efficacy of fractional flow reserve (FFR)-guided revascularization in different clinical settings. Aim: To evaluate the long-term outcome of an FFR-deferred strategy in daily practice. Methods: The Clinical Outcome of FFR-guided Revascularization Strategy of Coronary Lesions (HALE-BOPP) is an investigator-initiated, multicenter, international prospective study consecutively enrolling patients who underwent FFR measurement on at least one vessel. According to decision-making workflow and treatment, vessels were classified in three subgroups: i) angio-revascularized, ii) FFR-revascularized, iii) FFR-deferred. The primary endpoint was the occurrence of target vessel failure (TVF, cardiac death, target vessel myocardial infarction and ischemia-driven target vessel revascularization). The analysis is carried out at vessel- and patient-level. Results: Overall, 1305 patients with 2422 diseased vessels fulfilled criteria for the present analysis. Wire-related pitfalls and transient adenosine-related side effects occurred in 0.8% (95%CI 0.4%-0.1%) and 3.3% (95% 2.5%-4.3%) of cases, respectively. In FFR-deferred vessels the overall incidence rate of TVF was 0.024% (95%CI 0.019-0.031) lesion/year. After a median follow-up of 3.5 years, the occurrence of TVF was 6%, 7% and 11.7% in FFR-deferred, FFR-revascularized and angio-revascularized vessels, respectively. As compared to angio-revascularized vessels, FFR-guided vessels (both FFR-revascularized and FFR-deferred vessels) showed a lower TVF incidence rate lesion/year (0.029, 95%CI 0.024-0.034 vs. 0.049, 95%CI 0.040-0.061 respectively, p= 0.0001). This was consistent after correction for confounding factors and across subgroups of clinical interest. Patient-level analysis confirmed the lower occurrence of TVF in negative-FFR vs. positive-FFR subgroups. Conclusions: In a large prospective observational study, FFR-based strategy for the deferral of coronary lesions is reliable and safe and associated with good long-term outcome.